Melatonin restrains angiogenic factors in triple-negative breast cancer by targeting miR-152-3p: In vivo and in vitro studies - Marques, Jéssica H.M. (2018)
Aims: Breast cancer represents the second most prevalent tumor-related cause of death among women. Although studies have already been published regarding the association between breast tumors and miRNAs, this field remains unclear. MicroRNAs (miRNAs) are defined as non-coding RNA molecules, and are known to be involved in cell pathways through the regulation of gene expression. Melatonin can regulate miRNAs and genes related with angiogenesis. This hormone is produced naturally by the pineal gland and presents several antitumor effects. The aim of this study was to understand the action of melatonin in the regulation of miRNA-152-3p in vivo and in vitro. Main methods: In order to standardize the melatonin treatment in the MDA-MB-468 cells, we carried out the cell viability assay at different concentrations. PCR Array plates were used to identify the differentiated expression of miRNAs after the treatment with melatonin. The relative quantification of the target gene expression (IGF-IR, HIF-1α and VEGF) was performed by real-time PCR. For the tumor development, MDA-MB-468 cells were implanted in female BALB/c mice, and treated or not treated with melatonin. Moreover, the quantification of the target genes protein expression was performed by immunocytochemistry and immunohistochemistry. Key findings: Relative quantification shows that the melatonin treatment increases the gene expression of miR-152-3p and the target genes, and decreased protein levels of the genes both in vitro and in vivo. Significance: Our results confirm the action of melatonin on the miR-152-3p regulation known to be involved in the progression of breast cancer.